(untitled) (Physical Education, Health and Social Sciences, 2025)
This study examines the impact of malnutrition on lung function in adolescents using peak expiratory flow rate (PEFR) measurements. A cross-sectional analysis of 300 participants revealed varying levels of malnutrition and PEFR.